The systemic cellular immune response against allogeneic mesenchymal stem cells is influenced by inflammation, differentiation and MHC compatibility: in vivo study in the horse - Cequier, Alina; Vázquez, Francisco José; Vitoria, Arantza; Bernad, Elvira; Fuente, Sara; Serrano, María Belén; Zaragoza, María Pilar; Romero, Antonio; Rodellar, Clementina; Barrachina, Laura (Frontiers in Veterinary Science, 2024)
The effectiveness and safety of allogeneic mesenchymal stem/stromal cells (MSCs) can be affected by patient's immune recognition. Thus, MSC immunogenicity and their immunomodulatory properties are crucial aspects for therapy. Immune responses after allogeneic MSC administration have been reported in different species, including equine. Interactions of allogenic MSCs with the recipient's immune system can be influenced by factors like matching or mismatching for the major histocompatibility complex (MHC) between donor-recipient, and by the levels of MHC expression in MSCs. The latter can vary upon MSC inflammatory exposure or differentiation, such as chondrogenic induction, being making both priming and differentiation interesting therapeutic strategies. This study investigated the systemic in vivo immune cellular response against allogeneic equine MSCs in these situations.Either MSCs in basal conditions (MSC-naïve), pro-inflammatory primed (MSC-primed) or chondrogenically differentiated (MSC-chondro) were repeatedly administered subcutaneously into autologous, MHC-matched or MHC-mismatched allogeneic equine recipients. At different time-points after each administration, lymphocytes were obtained from recipient horses and exposed in vitro to the same type of MSCs to assess the proliferative response of different T cell subsets (cytotoxic, helper, regulatory), B cells, and interferon gamma (IFNγ) secretion.Higher proliferative response of helper and cytotoxic T lymphocytes and IFNγ secretion was observed in response to all types of MHC-mismatched MSCs over MHC-matched ones. MSC-primed produced the highest immune response, followed by MSC-naïve, and MSC-chondro. However, MSC-primed activated Treg and had a mild effect on B cells, and the response after their second administration was similar to the first one. On the other hand, both MSC-chondro and MSC-naïve barely induced Treg response but promoted B lymphocyte activation, and proportionally induced a higher cell response after the second administration.In conclusion, both the type of MSC conditioning and the MHC compatibility influenced systemic immune recognition of equine MSCs after single and repeated administrations, but the response was different. Selecting MHC-matched donors would be particularly recommended for MSC-primed and repeated MSC-naïve administrations. While MHC-mismatching in MSC-chondro would be less critical, B cell response should not be ignored. Comprehensively investigating the in vivo immune response against equine allogeneic MSCs is crucial for advancing veterinary cell therapies.